PREVALENCE AND INFLUENCE OF AGE AND BREED ON PROSTATIC DISEASES IN DOGS - MENON, KIREN; DEVARAJ, M; KRISHNASWAMY, A; HONNAPPA, T G (The Indian Journal of Animal Reproduction, 2011)
A study was conducted to screen the prevalence of prostatic diseases in intact male dogs over the age of fiveyears and effect of age and breed on the incidence of the• disease. An overall incidence of 1.34 percent wasrecorded in the present study. Dobermann (8.1%), GSD (3.31%) and Non- descript/Mongrel dogs (1.98%) were the only three breeds affected by the disease among the screened dogs. Average age of the affected animals was 8.70±0. 76 years with a range of 5-13 years.
Keywords: Dog; Prostate; Prevalence; Age; Breed